Hard carbon material, preparation method thereof, pole piece, application and electrochemical device

Through heat treatment, carbonization treatment and carbon coating, hard carbon materials with large closed-cell volumes were prepared, which solved the problem of low battery efficiency in the first time due to the small closed-cell volume of existing hard carbon materials, and achieved battery performance promote.

CN119447239AInactive Publication Date: 2025-02-14SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411565943.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The closed-cell volume of existing hard carbon materials is small, resulting in poor efficiency of assembled batteries for the first time.

Method used

By heat treatment, carbonization and carbon coating of the mixture of carbon precursor and activator, a hard carbon material with a large closed-cell volume is prepared.

Benefits of technology

Improves the electrochemical performance of the battery, especially the first-time Coulomb efficiency, and is suitable for the negative electrode material of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447239A_ABST
    Figure CN119447239A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon material, a preparation method thereof, a pole piece, application and an electrochemical device. The preparation method of the hard carbon material comprises the following steps: sequentially carrying out heat treatment, carbonization treatment and carbon coating on a mixture of a carbon precursor and an activating agent to obtain the hard carbon material, the carbonization treatment temperature is higher than the heat treatment temperature; the heat treatment temperature is 700-900 DEG C; the hard carbon material prepared by the invention has a relatively large closed pore volume, and a battery assembled by the hard carbon material has relatively good electrochemical performance, and particularly has relatively good initial coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon material and a preparation method, a pole piece, an application and an electrochemical device thereof. Background Art

[0002] The energy crisis and environmental pollution caused by the consumption of fossil fuels have attracted widespread attention, and my country has also set goals to deal with the energy crisis. In order to achieve this goal, it is urgent to efficiently utilize renewable clean energy such as solar energy, wind energy, tidal energy and geothermal energy to reduce carbon emissions. However, the above renewable energy sources often have the characteristics of periodicity and intermittency, and direct use is often difficult to match the needs of the power grid, and may even damage the transmission facilities. Secondary ion batteries have the advantages of high energy density, stable operation and low maintenance cost, and are an ideal choice for large-scale energy storage devices. Although lithium-ion batteries have many advantages, the shortage of lithium resources, high cost and poor safety limit the application of lithium-ion batteries in large-scale energy storage devices. Compared with lithium-ion batteries, sodium-ion batteries have become an ideal choice in the field of large-scale energy storage due to their abundant sodium resources, relatively low cost and good safety. Because hard carbon materials have many advantages such as high sodium storage capacity, low sodium storage voltage and good cycle performance, they have become the most promising negative electrode materials for sodium-ion batteries.

[0003] The precursors of hard carbon mainly include biomass, asphalt and coal-based, which have the advantages of wide sources, low cost, high carbon content and diversified structures. However, the aromatic structures in most precursors tend to develop in the long range during high-temperature carbonization. The single and restricted intercalation process is not conducive to the improvement of the sodium storage capacity of hard carbon. In contrast, short-range ordered graphite-like crystallites and rich closed-pore structures are the key to the rapid and high-density deintercalation of sodium ions.

[0004] Therefore, in order to further improve the energy density and cycle stability of sodium-ion batteries, it is urgent to develop a new method for preparing hard carbon materials to obtain hard carbon materials with high closed-pore capacity, moderate specific surface area and unique microstructure to meet the performance requirements of sodium-ion battery negative electrode materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defect that the closed pore volume of the hard carbon material in the prior art is small, resulting in poor first coulombic efficiency of the assembled battery, and provide a hard carbon material and its preparation method, pole piece, application and electrochemical device. The hard carbon material prepared by the present invention has a large closed pore volume, and the battery assembled from the hard carbon material has better electrochemical performance, especially better first coulombic efficiency.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The present invention provides a method for preparing a hard carbon material, which comprises the following steps: subjecting a mixture of a carbon precursor and an activator to heat treatment, carbonization treatment and carbon coating in sequence to obtain the hard carbon material; the temperature of the carbonization treatment is higher than the temperature of the heat treatment; the temperature of the heat treatment is 700-900°C.

[0008] In the present invention, the type of the carbon precursor may be conventional in the art, preferably one or more of biomass-based materials, asphalt-based materials and coal-based materials, such as biomass-based materials, asphalt-based materials or coal-based materials.

[0009] Among them, the type of biomass-based material is preferably one or more of coconut shell, rice shell, peanut shell, walnut shell, peanut shell, bamboo, cellulose, lignin and hazelnut shell, such as coconut shell, cellulose or walnut shell.

[0010] The type of the asphalt-based material is preferably one or more of petroleum asphalt, coal tar asphalt and mesophase asphalt, such as petroleum asphalt.

[0011] The type of the coal-based material is preferably one or more of bituminous coal, sub-bituminous coal and anthracite, such as anthracite.

[0012] In the present invention, the residual carbon rate of the carbon precursor may be 35%-50%, preferably 40%-45%, for example 42.85%. The residual carbon rate is calculated by the mass change of the carbon precursor before and after calcination at 1100±100°C in a nitrogen atmosphere.

[0013] In the present invention, the type of the activator may be one or more of H3PO3, ammonium phosphate, diammonium phosphate, diammonium hydrogen phosphate, ammonium polyphosphate, KOH, NaOH, ZnCl2, K2CO3, KHCO3, zinc acetate, basic zinc carbonate, zinc gluconate, melamine and urea, for example, H3PO3, KOH, zinc acetate, basic zinc carbonate, NaOH or ZnCl2.

[0014] In the present invention, the mass ratio of the carbon precursor to the activator may be 1:(0.1-10), preferably 1:(0.8-5), for example 1:1, 1:2, 1:3 or 1:4.

[0015] In the present invention, the mixture of the carbon precursor and the activator preferably further comprises a solvent. The type of the solvent can be conventional in the art, such as deionized water.

[0016] In the present invention, the method for preparing the mixture of the carbon precursor and the activator preferably comprises the following steps: impregnating, stirring and drying the carbon precursor, the activator and the solvent.

[0017] Wherein, the mass ratio of the carbon precursor to the deionized water is preferably 1:(0.5-13), for example 1:10.

[0018] The mixing time is preferably 1-24 hours, such as 10 hours.

[0019] Wherein, the stirring frequency is preferably 1-20HZ, such as 15HZ.

[0020] The drying operation may be conventional in the art, such as drying in a blast drying oven. The drying temperature may be 50-250° C., such as 160° C. The drying time may be 5-24 h, such as 12 h.

[0021] In the present invention, the heat treatment is preferably carried out under an inert atmosphere. The inert atmosphere is preferably one or more of nitrogen, argon and helium, such as nitrogen. The inlet volume of the inert atmosphere may be 0.1-2 dL / min, such as 0.3 or 0.5 dL / min.

[0022] In the present invention, the heat treatment equipment can be conventional in the art, such as a reactor. During the heat treatment, stirring is preferably performed. The stirring frequency can be 3-20 Hz, such as 5 or 10 Hz.

[0023] In the present invention, the temperature of the heat treatment may be 750-850°C, preferably 780-880°C, such as 800 or 850°C.

[0024] In the present invention, the heat treatment time may be 0.5-8 h, preferably 1-5 h, such as 3 or 4 h.

[0025] In the present invention, after the heat treatment and before the carbonization treatment, a crushing step is preferably performed. After the crushing, an intermediate material can be obtained. The crushing method can be conventional in the art, preferably mechanical crushing, ball milling or air flow crushing, such as air flow crushing. The end point of the crushing can be that the particle size of the intermediate material is 7-20 μm, such as 7 or 10 μm.

[0026] In the present invention, the equipment for the carbonization treatment can be conventional in the art, such as a box furnace. During the carbonization treatment, the intermediate material is preferably placed in a crucible.

[0027] In the present invention, the carbonization treatment is preferably carried out under an inert atmosphere. The inert atmosphere is preferably one or more of nitrogen, argon and helium, such as nitrogen. The inlet volume of the inert atmosphere may be 0.1-2 dL / min, such as 1 dL / min.

[0028] In the present invention, the temperature of the carbonization treatment may be 900-1600°C, preferably 1200-1500°C, such as 1300 or 1400°C.

[0029] In the present invention, the carbonization treatment time may be 0.5-6 hours, preferably 1-3 hours, such as 2 hours.

[0030] In the present invention, after the carbonization treatment and the carbon coating, a cooling step is preferably performed. The end point of the cooling can be room temperature, generally 20-30°C.

[0031] In the present invention, the carbon coating equipment may be conventional in the art, such as a coating kettle.

[0032] In the present invention, the coating agent used in the carbon coating may be a conventional carbon source in the art, such as asphalt and / or resin. The residual carbon rate of the coating agent used in the carbon coating is preferably 35%-55%, such as 39%, 45% or 53%. The residual carbon rate is calculated by using the mass change of the carbon precursor before and after calcination at 1100±100°C under a nitrogen atmosphere. The softening point of the coating agent used in the carbon coating may be 100-300°C, preferably 102-260°C, such as 253.2, 156.5 or 104.5°C.

[0033] In the present invention, the amount of the coating agent used in the carbon coating can be 1%-55% of "the mass of the carbonized product obtained by heat treating and carbonizing the mixture of the carbon precursor and the activator in sequence", preferably 3%-10%, for example 5%, 8% or 9%.

[0034] In the present invention, the equipment for carbon coating can be conventional in the art, such as a box furnace. During carbon coating, the material is preferably placed in a crucible.

[0035] In the present invention, the carbon coating temperature may be 900-1600°C, preferably 1000-1500°C, such as 1100, 1200, 1300 or 1400°C.

[0036] In the present invention, the carbon coating time may be 0.5-6 hours, preferably 1-5 hours, such as 4 hours.

[0037] In the present invention, after the carbon coating, a cooling step is preferably performed. The end point of the cooling can be room temperature, generally 20-30°C.

[0038] The present invention also provides a hard carbon material, which is obtained by the preparation method as described above.

[0039] In the present invention, the D50 of the hard carbon material may be 5-8 μm, preferably 5.2-6.5 μm, for example 5.9, 5.8, 6.2, 5.5, 5.7, 6.4 or 6.0 μm.

[0040] In the present invention, the true density of the hard carbon material can be 1-2.5 g / cm 3 , preferably 1.2-2.3 g / cm 3 , for example 2.11, 2.09, 2.08, 2.06, 2.05, 2.03 or 2.00 g / cm 3 .

[0041] In the present invention, the specific surface area of ​​the hard carbon material may be 2-10 m 2 / g, preferably 2.1-8.8m 2 / g, for example 8.47, 5.43, 5.32, 5.23, 4.33, 4.32, 3.82, 3.72, 3.54 or 2.31 m 2 / g.

[0042] The present invention also provides a hard carbon material, which comprises porous carbon and a carbon layer coated on the surface of the porous carbon; the closed pore volume of the hard carbon material is 0.03-0.07cm 3 / g.

[0043] In the present invention, the closed pore volume of the hard carbon material is preferably 0.031-0.06 cm 3 / g, for example, 0.0575, 0.0501, 0.0453, 0.0429, 0.0383, 0.0360 or 0.0315 cm 3 / g.

[0044] The present invention also provides a pole piece, which comprises the hard carbon material as described above.

[0045] In the present invention, preferably, the electrode sheet is a negative electrode sheet.

[0046] The present invention also provides an application of the pole piece as described above in an electrochemical device.

[0047] The present invention also provides an electrochemical device, which comprises the pole piece as described above.

[0048] In the present invention, the electrochemical device is preferably a sodium ion battery.

[0049] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0050] The reagents and raw materials used in the present invention are commercially available.

[0051] The positive and progressive effects of the present invention are:

[0052] (1) In the present invention, the micropores that cannot be closed after carbonization treatment can be converted into closed pores through the coating technology, and more closed pore structures are generated to increase the sodium storage capacity. The prepared hard carbon material has high capacity performance, first coulomb efficiency and excellent rate performance when used as a battery (especially a sodium ion battery).

[0053] (2) The preparation method of the present invention has a simple process and uses low-cost raw materials, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is the SEM image of the hard carbon material prepared in Example 1.

[0055] Figure 2 This is the SEM image of the hard carbon material prepared in Comparative Example 1.

[0056] Figure 3 It is a constant current charge and discharge curve diagram of the battery assembled with the hard carbon materials prepared in Example 1 and Comparative Example 1 at a current density of 0.1C. DETAILED DESCRIPTION

[0057] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0058] Example 1

[0059] (1) Impregnation: The crushed coconut shell raw material (residual carbon rate is 42.85%, D50 is 15 μm), H3PO3 and deionized water are mixed at a mass ratio of 1:1:10 at a stirring frequency of 15 Hz for 10 h for uniform impregnation, and then the material is filtered and placed in a forced air drying oven, and dried at 160° C. for 12 h to obtain a mixture of coconut shell raw material and H3PO3;

[0060] (2) Heat treatment: Add the prepared coconut shell raw material and H3PO3 mixture into a reactor and pass nitrogen gas at an air intake of 0.3 dL / min and a stirring frequency of 10 Hz, and heat treat at 800°C for 3 h, followed by air flow pulverization to obtain an intermediate material; the D50 of the intermediate material is 7 μm;

[0061] (3) Carbonization treatment: The intermediate material is placed in a crucible and carbonized at 1400°C for 2 h in a box furnace under a nitrogen atmosphere with an air intake of 1 dL / min. After the carbonization is completed, the material is cooled to room temperature and taken out of the box furnace to obtain a carbonized product.

[0062] (4) Carbon coating: Add 5 wt% of asphalt coating agent 1 (residual carbon rate is 53%, softening point is 253.2°C) to the carbonized product, and use a coating kettle to coat the product to obtain a coated material; put the coated material into a crucible, and use a box furnace to carbonize it at 1100°C for 4 hours in an inert gas atmosphere. After the carbonization, cool it to room temperature and take the material out of the box furnace to obtain a hard carbon material.

[0063] Example 2

[0064] The only difference from Example 1 is that H3PO3 is replaced by KOH.

[0065] Example 3

[0066] The only difference from Example 1 is that H3PO3 is replaced by zinc acetate.

[0067] Example 4

[0068] The only difference from Example 1 is that H3PO3 is replaced by basic zinc carbonate.

[0069] Example 5

[0070] The only difference from Example 1 is that H3PO3 is replaced by NaOH.

[0071] Example 6

[0072] The only difference from Example 1 is that H3PO3 is replaced by zinc chloride.

[0073] Example 7

[0074] The only difference from Example 1 is that asphalt coating agent 1 is replaced by asphalt coating agent 2, the residual carbon rate is 45%, and the softening point is 156.5°C.

[0075] Example 8

[0076] The only difference from Example 1 is that the asphalt coating agent 1 is replaced by the asphalt coating agent 3, the residual carbon rate is 39%, and the softening point is 104.5°C.

[0077] Example 9

[0078] The only difference from Example 1 is that the heat treatment temperature is 700°C.

[0079] Example 10

[0080] The only difference from Example 1 is that the heat treatment temperature is 900°C.

[0081] Comparative Example 1

[0082] The only difference from Example 1 is that the preparation process does not include step (4) and step (5).

[0083] Comparative Example 2

[0084] The only difference from Example 1 is that the heat treatment temperature is 1200°C.

[0085] Comparative Example 3

[0086] The only difference from Example 2 is that the heat treatment temperature is 600°C.

[0087] Comparative Example 4

[0088] The only difference from Example 6 is that the heat treatment temperature is 600°C.

[0089] Effect Example 1

[0090] The hard carbon materials obtained in Example 1 and Comparative Example 1 were observed by SEM, and the results were as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 By comparison, Figure 1 The particles in the embodiment are obviously more rounded, and a uniform layer of material is obviously added to the surface. This shows that, compared with comparative example 1, embodiment 1 does form a uniform coating layer after coating.

[0091] The D50 particle size, true density and specific surface area of ​​the hard carbon materials obtained in the above embodiments and comparative examples were tested. The D50 particle size was tested using Malvern 3000. The true density and closed-pore volume were both tested using the helium method, and the test method is as follows: the true density test was performed on AccuPycⅡ1340, with helium as the working gas. The principle is based on the fact that the aerodynamic diameter and van der Waals radius of helium (He) are small enough to enter most of the open pores in the carbon material, but not the closed pores, so He is usually used to characterize the true density of the material. In theory, highly oriented pyrolytic graphite (HOPG) has a perfect layered structure without open and closed pores. It is the carbon material with the highest true density (except diamond) and can be used as a standard substance for comparing the true density of other materials. The true density of HOPG is 2.26 gcm -3 , so the closed pore volume of the hard carbon materials obtained in the embodiments and comparative examples can be obtained by the following formula: Among them, P true It represents the true density of the hard carbon material obtained in Examples or Comparative Examples.

[0092] The test method for specific surface area is: nitrogen isothermal adsorption and desorption test. The instrument used is a fully automatic specific surface area and porosity analyzer, model is American Micromeritics ASAP 2460; the degassing temperature is 300°C, and the degassing time is 4h.

[0093] The test results are shown in Table 1.

[0094] Table 1

[0095]

[0096]

[0097] It can be seen from Table 1 that compared with Examples 1-10, Example 1 does not undergo carbon coating, and the hard carbon material obtained has a larger specific surface area and a smaller closed pore volume; when the heat treatment temperature of Examples 2-4 is higher or lower, the hard carbon material obtained has a larger specific surface area and a smaller closed pore volume.

[0098] Effect Example 2

[0099] The hard carbon material prepared in the embodiment or comparative example is mixed with a binder polyvinylidene fluoride PVDF and a conductive agent Super-P in a mass ratio of 8:1:1, and N-methylpyrrolidone NMP is added as a dispersant to prepare a slurry, which is evenly coated on a copper foil with a thickness of 8 μm, dried in a drying oven at 100°C for 12 h, and pressed into a 12 mm electrode sheet for use. Metallic sodium is used as a counter electrode, and a two-component mixed solvent of 1M NaPF6, ethylene carbonate EC: dimethyl carbonate DMC, is mixed in a volume ratio of 1:1 to form an electrolyte. A glass fiber of model GF / A is used as a diaphragm. The cells are assembled into button cells in an argon-filled glove box. The button cells are tested on the CT-3002A battery testing system of Wuhan Blue Electric Battery Testing Equipment Co., Ltd. with a charge and discharge voltage limited to 0.001 to 2.0 V. The first reversible capacity and the first coulomb efficiency are tested. The first coulomb efficiency is calculated as follows: first coulomb efficiency = first charge capacity / first discharge capacity.

[0100] The test results are shown in Table 2 and Figure 3 shown.

[0101] Table 2

[0102]

[0103]

[0104] It can be seen from Table 3 that, compared with Examples 1-10, Example 1 does not perform carbon coating, and the battery capacity performance and the first coulombic efficiency of the hard carbon material assembled obtained are poor; when the heat treatment temperature of Examples 2-4 is higher or lower, the battery capacity performance and the first coulombic efficiency of the hard carbon material assembled obtained are poor.

[0105] Figure 3 The constant current charge and discharge curves of the battery assembled with the hard carbon material prepared in Example and Comparative Example 1 at a current density of 0.1C are shown. Figure 3It can be seen that compared with Comparative Example 1, Example 1 was carbon-coated, and its first reversible capacity and first coulombic efficiency were significantly improved.

[0106] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process equipment and process flow, and it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be realized. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, and selection of specific methods all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: The method comprises the following steps: subjecting a mixture of a carbon precursor and an activator to heat treatment, carbonization treatment and carbon coating in sequence to obtain the hard carbon material; the temperature of the carbonization treatment is higher than the temperature of the heat treatment; the temperature of the heat treatment is 700-900°C.

2. The method for preparing a hard carbon material according to claim 1, characterized in that: The method for preparing the hard carbon material satisfies one or more of the following conditions (1) to (4), (1) The type of the carbon precursor is one or more of a biomass-based material, an asphalt-based material and a coal-based material, such as a biomass-based material, an asphalt-based material or a coal-based material; Wherein, the type of the biomass-based material is preferably one or more of coconut shell, rice shell, peanut shell, walnut shell, groundnut shell, bamboo, cellulose, lignin and hazelnut shell, such as coconut shell, cellulose or walnut shell; Wherein, the type of the asphalt-based material is preferably one or more of petroleum asphalt, coal tar asphalt and mesophase asphalt, such as petroleum asphalt; The type of the coal-based material is preferably one or more of bituminous coal, sub-bituminous coal and anthracite, such as anthracite; (2) The residual carbon rate of the carbon precursor is 35%-50%, preferably 40%-45%, for example 42.85%; (3) the type of the activator is one or more of H3PO3, ammonium phosphate, diammonium phosphate, diammonium hydrogen phosphate, ammonium polyphosphate, KOH, NaOH, ZnCl2, K2CO3, KHCO3, zinc acetate, basic zinc carbonate, zinc gluconate, melamine and urea, for example, H3PO3, KOH, zinc acetate, basic zinc carbonate, NaOH or ZnCl2; and, (4) The mass ratio of the carbon precursor to the activator is 1:(0.1-10), preferably 1:(0.8-5), for example 1:1, 1:2, 1:3 or 1:

4.

3. The method for preparing a hard carbon material according to claim 1, characterized in that: The method for preparing the hard carbon material satisfies one or more of the following conditions (1) to (12), (1) The heat treatment is carried out under an inert atmosphere; the inert atmosphere is preferably one or more of nitrogen, argon and helium, such as nitrogen; the inlet volume of the inert atmosphere is preferably 0.1-2 dL / min, such as 0.3 or 0.5 dL / min; (2) The heat treatment temperature is 750-850°C, preferably 780-880°C, for example 800 or 850°C; (3) The heat treatment time is 0.5-8h, preferably 1-5h, for example 3 or 4h; (4) The carbonization treatment is carried out under an inert atmosphere; the inert atmosphere is preferably one or more of nitrogen, argon and helium, such as nitrogen; the inlet volume of the inert atmosphere is preferably 0.1-2 dL / min, such as 1 dL / min; (5) The temperature of the carbonization treatment is 900-1600°C, preferably 1200-1500°C, for example 1300 or 1400°C; (6) The carbonization treatment time is 0.5-6h, preferably 1-3h, for example 2h; (7) The coating agent used in the carbon coating is asphalt and / or resin; (8) The residual carbon rate of the coating agent used in the carbon coating is 35%-55%, for example, 39%, 45% or 53%; (9) The softening point of the coating agent used in the carbon coating is 100-300°C, preferably 102-260°C, for example 253.2, 156.5 or 104.5°C; (10) The amount of the coating agent used in the carbon coating is 1%-55% of "the mass of the carbonized product obtained by heat treating and carbonizing the mixture of the carbon precursor and the activator in sequence", preferably 3%-10%, for example 5%, 8% or 9%; (11) The carbon coating temperature is 900-1600°C, preferably 1000-1500°C, for example 1100, 1200, 1300 or 1400°C; and, (12) The carbon coating time is 0.5-6 hours, preferably 1-5 hours, for example 4 hours.

4. A hard carbon material, characterized in that: The method is obtained by the preparation method described in any one of claims 1 to 3.

5. The hard carbon material according to claim 4, characterized in that The hard carbon material satisfies one or more of the following conditions (1)-(3): (1) The D50 of the hard carbon material is 5-8 μm, preferably 5.2-6.5 μm, for example 5.9, 5.8, 6.2, 5.5, 5.7, 6.4 or 6.0 μm; (2) The true density of the hard carbon material is 1-2.5 g / cm 3 , preferably 1.2-2.3 g / cm 3 , for example 2.11, 2.09, 2.08, 2.06, 2.05, 2.03 or 2.00 g / cm 3 ; and, (3) The specific surface area of ​​the hard carbon material is 2-10 m 2 / g, preferably 2.1-8.8m 2 / g, for example 8.47, 5.43, 5.32, 5.23, 4.33, 4.32, 3.82, 3.72, 3.54 or 2.31 m 2 / g.

6. A hard carbon material, characterized in that It comprises porous carbon and a carbon layer coated on the surface of the porous carbon; the closed pore volume of the hard carbon material is 0.03-0.07 cm3 / g.

7. The hard carbon material according to claim 6, characterized in that The closed pore volume of the hard carbon material is 0.031-0.06 cm 3 / g, for example, 0.0575, 0.0501, 0.0453, 0.0429, 0.0383, 0.0360 or 0.0315 cm 3 / g.

8. A pole piece, characterized in that: It comprises the hard carbon material as claimed in any one of claims 4 to 7.

9. Use of the electrode piece according to claim 8 in an electrochemical device.

10. An electrochemical device, characterized in that: It includes a pole piece as claimed in claim 8; The electrochemical device is preferably a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery negative electrode carbon material with porous core-shell structure

    CN118083943A

Cited By

  • Bio-based hard carbon for negative electrode material and preparation method of bio-based hard carbon

    CN121202115A